Measurement and Analysis of Noise Levels from Loudspeakers on Public Transportation in Kupang, East Nusa Tenggara - Theophilus Wellem; Yessica Nataliani; Danny Manongga; Hendry Hendry; Darmawan Utomo; Ivanna K. Timotius; Daniel D. Kameo; Aldi Lasso; Winsy C.D Weku (Jurnal Ilmiah Sains, 2024)
The government is very concerned about the threshold value of human hearing that causes permanent noise-induced hearing loss (NIHL), such as noise caused by public transportation (bemo) in Kupang. This research aims to increase the awareness of the bemo user in Kupang to prevent hearing loss due to noise from bemo audio devices. Noise measurements due to public transportation are usually carried out outside the vehicle, for example, on the street, but in this study, measurements were carried out inside the vehicle (bemo). Data was obtained from (1) Data on sound intensity in public transport taken manually using a Sound Pressure Level (SPL) meter and (2) Data on the working hours of the drivers taken manually by asking how long they drive in a day. The results of  of each route and the average of  of eight routes showed a sound intensity above the threshold set by the government, i.e., 70 dB. Routes 1 and 3 are bemo routes that need attention because they have maximum sound intensity of more than 100 dB and are included in the Very Loud category. Meanwhile, the other routes are included in the Loud category. Furthermore, the average time a driver stays in a bemo daily is 13.5 hours, which concluded that all drivers are at risk of hearing loss. Therefore, special attention is needed from the government because this can result in driver hearing loss.   Keywords: Bemo; Kupang; Noise-induced hearing loss; Public transportation; Sound intensity